Social isolation and quarantine effects over the subjective well-being of Chileans during the COVID-19 outbreak - Ahumada, Pedro San Martín (2020)
The subjective well-being of a sample of 175 adults from Santiago de Chile, who have been between 1 and 3 weeks in social isolation and/or quarantine, was analyzed through the Positive and Negative Affect Scale adapted by Arancibia. To that end, the averages of both scales were compared with the correlative critical values from the same instrument validation study. The main results showed that the group under social isolation had a lower average raw score in the expression of positive affect and higher in negative affect, with both being significant. In addition, disparate results were obtained for the scales when calculating the magnitude of the effect (Cohen's d)